PELATIHAN GURU BAHASA INGGRIS DALAM PENGUATAN PROFESIONALITAS GURU MELALUI PENULISAN ARTIKEL PENELITIAN - Anaktototy, Karolis; Monica, Monica; Patty, Jusak (Universitas Pattimura, 2023)
Training in research article writing is essential for English language teachers to strengthen their academic competence and enhance professionalism. This article discusses implementing training involving English language teachers in Ambon City, Maluku Province. Using an interactive and practical approach, the training comprises workshops, practical exercises, reading materials, technological utilization, and feedback with evaluation. Satisfaction survey evaluations indicate that most participants responded positively to the content, benefits, and discussion sessions. However, some expressed dissatisfaction with the clarity of materials and event organization. Future improvements are recommended through more detailed material development and efficient time management. Overall, the training met participants' fundamental needs. However, evaluations catalyze enhancing material quality, event organization, and training approaches to elevate the academic contributions of English language teachers.